Institutions and Mechanisms for Internal Conflict Resolution: Legal and Non-Legal Means in Resolving Dispute and Attaining Justice in Malaysia - Khairil Azmin Mokhtar (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2016)
Seeking justice is a noble cause and dispensing justice is an obligation that the state must fulfill. Under the doctrine of separation of powers courts exist to protect people and their rights, to guarantee fairness and justice for all. The task to combat injustices, produce a just ordering of society, ensure a fair distribution of material and legal resources, safeguard the rule of law, promote equality, ensure proportionality in punishment, and protect entitlements and legitimate expectations should not be put on the shoulders of judges and courts only. It must be spread out and shared by other institutions and by whatever means available